Challenges in the Evolution of the Medical Informatics Program at Heidelberg/Heilbronn (Germany) - Knaup, P.; Haag, M.; Leven, F. J.; Dickhaus, H. (Methods of Information in Medicine, 2009)
Objective: Health and medical informatics (HMI) is an evolving discipline. Therefore, evolving educational programs in HMI have to take a variety of requirements into account. The aim of this paper is to analyze these requirements and to compare them with the medical informatics program Heidelberg/Heilbronn, Germany.Methods: Systematic analysis of the IMIA recommendations on educating HMI, the Bologna declaration, current technological and health care developments and the results of graduates surveys.Results: The latest revision of the Heidelberg/ Heilbronn medical informatics program not only takes current developments into account but also realizes the IMIA recommendations, the Bologna declaration and graduates’ data and feedback obtained in structured surveys. The topics bioinformatics, IT security and tele-medicine were strengthened, taking major research and application trends into account. The program has been transformed into a consecutive bachelor/master program. It qualifies its graduates to work in the field of medical informatics as well as in informatics.Conclusions: Medical informatics is a very broad field. Programs have to make concessions to scope: It is not possible to provide profound knowledge and skills in computer science and also teach a variety of application areas like bioinformatics, public health informatics and clinical informatics in depth within one medical informatics program. Many graduate programs in various nations concentrate on providing HMI skills to health care professionals.
Keywords: Medical informatics; health informatics; education